Proapoptotic BIM Impacts B Lymphoid Homeostasis by Limiting the Survival of Mature B Cells in a Cell-Autonomous Manner - Liu, Rui; King, Ashleigh; Bouillet, Philippe; Tarlinton, David M.; Strasser, Andreas; Heierhorst, Jörg (Frontiers in Immunology, 2018)
The pro-apoptotic BH3-only protein BIM (Bcl2l11) plays key roles in the maintenance of multiple hematopoietic cell types. In mice, germline knockout or conditional pan-hematopoietic deletion of Bim results in marked splenomegaly and significantly increased numbers of B cells. However, it has remained unclear whether these abnormalities reflect the loss of cell-intrinsic functions of BIM within the B lymphoid lineage and, if so, which stages in the lifecycle of B cells are most impacted by the loss of BIM. Here we show that B lymphoid-specific conditional deletion of Bim during early development (i.e., in pro-B cells using Mb1-Cre) or during the final differentiation steps (i.e., in transitional B cells using Cd23-Cre) led to a similar >2-fold expansion of the mature follicular B cell pool. Notably, while the expansion of mature B cells was quantitatively similar in conditional and germline Bim-deficient mice, the splenomegaly was significantly attenuated after B lymphoid-specific compared to global Bim deletion. In vitro, conditional loss of Bim substantially increased the survival of mature B cells that were refractory to activation by lipopolysaccharide. Finally, we also found that conditional deletion of just one Bim allele by Mb1-Cre dramatically accelerated the development of Myc-driven B cell lymphoma, in a manner that was comparable to the effect of germline Bim heterozygosity. These data indicate that, under physiological conditions, BIM regulates B cell homeostasis predominantly by limiting the life-span of non-activated mature B cells, and that it can have additional effects on developing B cells under pathological conditions.